2003
DOI: 10.1074/jbc.m300913200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitinylation of the Cytosolic Domain of a Type I Membrane Protein Is Not Required to Initiate Its Dislocation from the Endoplasmic Reticulum

Abstract: Human cytomegalovirus US2 and US11 target newly synthesized class I major histocompatibility complex (MHC) heavy chains for rapid degradation by the proteasome through a process termed dislocation. The presence of US2 induces the formation of class I MHC heavy chain conjugates of increased molecular weight that are recognized by a conformation-specific monoclonal antibody, W6/32, suggesting that these class I MHC molecules retain their proper tertiary structure. These conjugates are properly folded glycosylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 36 publications
5
38
0
Order By: Relevance
“…3c, lane 8). Together, these observations suggest that dislocation of MHC class I HC in permeabilized US2 cells also involves ubiquitination in agreement with previous studies in intact cells, which showed that polyubiquitinated MHC class I HC is present in US2 cells treated with a proteasome inhibitor (17), and that removal of potential ubiquitin conjugation sites in MHC class I HC abolished its dislocation (18).…”
Section: An In Vitro Assay For Us2-mediatedsupporting
confidence: 80%
See 1 more Smart Citation
“…3c, lane 8). Together, these observations suggest that dislocation of MHC class I HC in permeabilized US2 cells also involves ubiquitination in agreement with previous studies in intact cells, which showed that polyubiquitinated MHC class I HC is present in US2 cells treated with a proteasome inhibitor (17), and that removal of potential ubiquitin conjugation sites in MHC class I HC abolished its dislocation (18).…”
Section: An In Vitro Assay For Us2-mediatedsupporting
confidence: 80%
“…The elimination of the antigen presenting MHC HC molecules from the ER membrane apparently allows viruses to escape detection by the host immune system. Both US11 and US2 directly bind MHC class I HC to initiate the retrotranslocation process, and both pathways involve ubiquitin, the 26 S proteasome, and a translocating chain-associated membrane protein-1 (15)(16)(17)(18)(19). Nonetheless, these two processes each posses its own unique features, indicating that these two viral proteins may use different retrotranslocation routes to dislocate MHC class I HC from the ER membrane.…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…Mutation of cytosolic tail lysines results in a marked loss of US2-induced ubiquitination of membrane-associated MHC I HCs, implying that TRC8 preferentially targets lysine residues in the MHC I tail (26). The mutant HC is, however, still dislocated, suggesting US2 may use alternative mechanisms of dislocation in the absence of accessible cytosolic lysines (26).…”
Section: Discussionmentioning
confidence: 94%
“…US2 interacts with the luminal domain of conformational, β2m-associated MHC I HC, but requires the MHC I transmembrane domain, and possibly tail residues, to mediate dislocation (22,25). Mutation of cytosolic tail lysines results in a marked loss of US2-induced ubiquitination of membrane-associated MHC I HCs, implying that TRC8 preferentially targets lysine residues in the MHC I tail (26). The mutant HC is, however, still dislocated, suggesting US2 may use alternative mechanisms of dislocation in the absence of accessible cytosolic lysines (26).…”
Section: Discussionmentioning
confidence: 99%
“…Using this system, cells can remove unwanted, degenerated, or excessively expressed proteins, thus maintaining cellular protein homeostasis. The ubiquitination pathway is known to regulate critical control points in multiple cellular processes, including receptor internalization, endosomal degradation, nuclear transport, and the turnover of several key cell cycle-regulating proteins [3][4][5]. The pathway involves a complex enzymatic cascade responsible for protein ubiquitination and degradation.…”
Section: Introductionmentioning
confidence: 99%